A instrumentalização mútua de religião e política na Câmara Municipal de Limeira-SP - Marcomini, Roberson Augusto (2024)
The purpose of this study is to investigate the growth of religious influence in the public sphere, focused on the City Council of Limeira, São Paulo. The research is based on a review of available literature on religion and politics, as well as an analysis of relevant documents including newspapers, videos, books, articles, websites, and interviews with councilors, political leaders, and religious leaders in the city. The study examines the intersection of politics and religion in the last two municipal legislatures (2016-2020 and 2021-2024). It aims to analyze the support of religious groups for aldermen in Limeira, as well as how this issue is addressed during election periods. Religious groups seek to elect their own representatives to the municipal legislature. The study of the relationship between religion and politics in Limeira is part of a larger sociological study about this matter in other cities across the country. By tracking the parliamentary actions of councilors with overt religious affiliations, the research aims to analyze their behavior on issues that impact or are of interest to the city's religious communities.